Effects of emotional valence and three-dimensionality of visual stimuli on brain activation: an fMRI study - Dores, A. R. (2013)
BACKGROUND: Examining changes in brain activation linked with emotion-inducing stimuli is essential to the study of emotions. Due to the ecological potential of techniques such as virtual reality (VR), inspection of whether brain activation in response to emotional stimuli can be modulated by the three-dimensional (3D) properties of the images is important. OBJECTIVE: The current study sought to test whether the activation of brain areas involved in the emotional processing of scenarios of different valences can be modulated by 3D. Therefore, the focus was made on the interaction effect between emotion-inducing stimuli of different emotional valences (pleasant, unpleasant and neutral valences) and visualization types (2D, 3D). However, main effects were also analyzed. METHODS: The effect of emotional valence and visualization types and their interaction were analyzed through a 3 × 2 repeated measures ANOVA. Post-hoc t-tests were performed under a ROI-analysis approach. RESULTS: The results show increased brain activation for the 3D affective-inducing stimuli in comparison with the same stimuli in 2D scenarios, mostly in cortical and subcortical regions that are related to emotional processing, in addition to visual processing regions. CONCLUSIONS: This study has the potential of clarify brain mechanisms involved in the processing of emotional stimuli (scenarios' valence) and their interaction with three-dimensionality.